Measuring level of knowledge about zoonoses: A scale development study - Kurt, Osman; Oguzöncül, Ayse Ferdane (Bayrakol Medical Publisher, 2022)
Aim: The scope validity was provided as the first step in the development of the scale in this methodological and cross-sectional study. Material and Methods: Item difficulty and discriminatory power index were calculated for each item. Exploratory factor analysis was used to determine the construct validity. The Cronbach alpha internal consistency coefficient was calculated to determine the reliability of the scale. The number of public health professionals working in the field, of which 403 (participation rate of 82%) could be reached, was 491. Results: The mean difficulty levelof the Zoonotic Knowledge Level Scale (ZKLS), with a Cronbach alpha value of 0.910, in which item-removed values varied between 0,903-0,908, was found as 0.68. Besides, it was observed that knowledge scores increased as the duration of public health professionals' expertise and their working time in the infectious diseases branch increased. The knowledge level of those who worked in the infectious diseases branch was significantly higher than those who did not. Discussion: As a result, this scale, developed on zoonoses, was found to be valid and reliable. However, its reliability in particular groups needs to be tested with more extensive studies to elucidate and prove its impact further and apply it to society's other fields.
Keywords: Zoonoses; Level of Knowledge; Scale Development; ZKLS; Reliability